Middle-Income Growth Traps - Agénor, Pierre-Richard; Canuto, Otaviano (World Bank, Washington, DC, 2012)
This paper studies the existence of middle-income growth traps in a two-period overlapping generations model of economic growth with two types of labor and endogenous occupational choices. It also distinguishes between "basic" and "advanced" infrastructure, with the latter promoting design activities, and accounts for a knowledge network externality associated with product diversification. Multiple steady-state equilibria may emerge, one of them taking the form of a low-growth trap characterized by low productivity growth and a misallocation of talent -- defined as a relatively low share of high-ability workers in design activities. Improved access to advanced infrastructure may help escape from that trap. The implications of other public policies, including the protection of property rights and labor market reforms, are also discussed.